The optical characterization of hydrogenated amorphous carbon thin films deposited by a DC-PECVD method - Sakrani, Samsudi (2003)
Diamond-like carbon (DLC) is a metastable form of amorphous carbon with attractive properties such as high hardness, low friction, chemical inertness and high wear resistance.